The long road to recovery: New York schools in the aftermath of the great recession - Rajashri Chakrabarti; Max Livingston (Federal Reserve Bank of New York, 2013)
Schools play a crucial role in human capital development, and were one of the many elements of government adversely affected by the Great Recession. Using a rich panel data set of New York State school districts and a trend-shift analysis, we examine how the funding and expenditure dynamics of districts have changed in the four years since the recession hit. We find that although the stimulus prevented major cuts to expenditures while it was in place, once the stimulus funding was used up districts faced strong budget constraints and made deep cuts to their expenditures. While state and local funding continue to be below trend, the role of funding schools has shifted more to local governments because of a cutback in state and federal aid. Breaking up expenditure into its primary categories, we see that instructional spending was preserved with the help of the stimulus money in 2010, but by 2012 instructional expenditure experienced a statistically and economically significant downward shift. We also examine heterogeneities in the effects by metropolitan area, looking at the major MSAs of New York. We find that Nassau sustained the largest cuts, while Buffalo sustained the smallest. These findings are instructive in that they shed light on how recessions and fiscal policy can affect school finance dynamics, and provide important lessons/insight for future policy and experiences of schools in financial distress.
Keywords: H40; I20; R10; R50; 330; school finance; recession; ARRA; federal stimulus